Valoración de la exposición a factores de riesgos químicos en los laboratorios de química en la sede Queri de la Universidad de Las Américas (Quito), y recomendaciones de medidas preventivas. - Olmedo Ron, Santiago (2016)
The constructivism is the most applied current in education. The student is responsible for generating their own knowledge on the basis of experience. This is very applicable in science where they can reinforce scientific knowledge with the corresponding laboratory analysis. However this is where the risk begins. At the laboratories, everybody is exposed to chemicals products, hot surfaces and sharp objects. All these objects can injure the user. The purpose of this research is to put in numbers the level of risk that someone is exposed to during an accident at the laboratories at the University of the Americas in Quito Ecuador. To reach this objective the NTP 330 has been applied. To start with the role of every laboratory user was determined. Then, each process was determined. Each process was assigned into a scale. Finally once the chi square method was determined, it was concluded that the process in general are correctable. Those actions can return to the laboratory as improvement into a safer place.